Towards Universal Health Coverage: Analyzing HWAR Policies in Palestine’s Complex Health Landscape [Letter] - Muttaqin MZ; Reba YA; Prasetya YY (Dove Medical Press, 2024)
M Zaenul Muttaqin,1,* Yansen Alberth Reba,2,* Yovian Yustiko Prasetya3,* 1Department of State Administration, Universitas Cenderawasih, Papua, Indonesia; 2Department of Guidance and Counseling, Universitas Cenderawasih, Papua, Indonesia; 3Department of Guidance and Counseling, Universitas Pancasakti Tegal, Tegal, Indonesia*These authors contributed equally to this workCorrespondence: M Zaenul Muttaqin, Department of State Administration, Universitas Cenderawasih, Papua, Indonesia, Email mzaenul69@gmail.com